Vitamin D receptor-modulated Hsp70/AT(1) expression may protect the kidneys of SHRs at the structural and functional levels - García, Isabel Mercedes (Springer Netherlands, 2013)
Previous hypertension studies have shown that low levels of vitamin D are linked to elevated renin–angiotensin system. The heat shock protein 70 regulates signaling pathways for cellular oxidative stress responses. Hsp70 has been shown to protect against angiotensin II-induced hypertension and exert a cytoprotective effect. Here, we wanted to evaluate whether the vitamin D receptor (VDR) associated with Hsp70/AT(1) expression may be involved in the mechanism by which paricalcitol provides renal protection in spontaneously hypertensive rats (SHRs). One-month-old female SHRs were treated for 4 months with vehicle, paricalcitol, enalapril, or a combination of both paricalcitol and enalapril. The following were determined: blood pressure; biochemical parameters; fibrosis; apoptosis; mitochondrial morphology; and VDR, AT(1) receptor, and Hsp70 expression in the renal cortex. Blood pressure was markedly reduced by enalapril or the combination but not by paricalcitol alone. However, VDR activation, enalapril or combination, prevented fibrosis, the number of TUNEL-positive apoptotic cells, mitochondrial damage, and NADPH oxidase activity in SHRs. Additionally, high AT(1) receptor expression, like low Hsp70 expression (immunohistochemical/immunofluorescence studies), was reversed in the renal cortices of paricalcitol- and/or enalapril-treated animals (SHRs), and these changes were most marked in the combination therapy group. Finally, all of the recovery parameters were consistent with an improvement in VDR expression. Data suggest that Hsp70/AT(1) modulated by VDR is involved in the mechanism by which paricalcitol provides renal protection in SHRs. We propose that low AT(1) expression through VDR induction could be a consequence of the heat shock response Hsp70-mediated cell protection.